Psychological Distress and All-Cause, Cardiovascular Disease, Cancer Mortality Among Adults with and Without Diabetes - De Moraes-Ferrari, G (Dove Medical Press Ltd, 2021)
Aim: To examine the association of psychological distress with all-cause, cardiovascular disease (CVD) and cancer mortality in US adults, and verified whether the associations differed between participants with and without diabetes. Methods: A total of 485,864 adults (446,288 without diabetes and 39,576 with diabetes) who participated in the National Health Interview Survey from 1997 to 2013 were linked to the National Death Index through December 31, 2015. Psychological distress was measured by the Kessler 6 distress scale (K6). Multivariable Cox proportional hazards regression models were performed to estimate hazard ratios (HR) and 95% confidence intervals (95% CI) for the association between psychological distress and mortality. Results: We ascertained 11,746 deaths (mean follow-up, 7. 7 years) among people with diabetes and 51,636 deaths (9.9 years) among those without diabetes. Psychological distress was associated with higher all-cause, CVD, and cancer mortality. Compared to non-diabetic adults without psychological distress, HRs (95% CI) were 1.07 (1.04 to 1.09) for mild, 1.26 (1.22 to 1.30) for moderate and 1.46 (1.38 to 1.55) for severe psychological distress. Compared to the same reference group, in diabetic participants the HRs were 1.39 (1.33 to 1.44) for no psychological distress, 1.59 (1.53 to 1.66) for mild, 1.90 (1.80 to 2.00) for moderate and 1.98 (1.82 to 2.17) for severe psychological distress. Similar associations were also observed for CVD and cancer mortality but with non-statistically significant interaction. Conclusion: Psychological distress was associated with higher mortality, particularly in participants with diabetes. Strategies to ameliorate psychological distress may be important to reduce mortality in this population. © 2021 Huang et al.